2022
DOI: 10.1128/spectrum.01596-21
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila Ameliorates Acetaminophen-Induced Liver Injury by Regulating Gut Microbial Composition and Metabolism

Abstract: Our work revealed that A. muciniphila attenuated APAP-induced liver injury by alleviating oxidative stress and inflammation in the liver, and its hepatoprotective effect was accompanied by activation of the PI3K/Akt pathway and mediated by regulation of the composition and metabolic function of the intestinal microbiota. This finding suggested that the microbial community is a non-negligible impact on drug metabolism and probiotic administration could be a potential therapy for drug-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 70 publications
5
85
0
Order By: Relevance
“…The function of Christensenellaceae_R_7_group is the same as that of Christensenellaceae ( Morotomi et al, 2012 ). Additionally, Candidatus_Saccharimonas species are positively correlated with propionic acid and butyric acid levels ( Xia et al, 2022 ) and play an important role in maintaining gut functions ( Xie et al, 2021 ). The relative abundance of the genus Akkermansia was greater in the FH group than in the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The function of Christensenellaceae_R_7_group is the same as that of Christensenellaceae ( Morotomi et al, 2012 ). Additionally, Candidatus_Saccharimonas species are positively correlated with propionic acid and butyric acid levels ( Xia et al, 2022 ) and play an important role in maintaining gut functions ( Xie et al, 2021 ). The relative abundance of the genus Akkermansia was greater in the FH group than in the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Oral Lactobacillus rhamnosus GG has been shown to protect against APAP-induced liver injury by activating Nrf2 via Lactobacillus-derived 5-methoxyindoleacetic acid [41]. Recent reports have shown that oral administration of Akkermansia muciniphila improved oxidative stress and inflammation to protect against APAP-induced liver injury, which was closely related to the remodeling of intestinal microflora and enhanced short-chain fatty acids (SCFAs) [42]. In this study, the hepatoprotective effect of BPP disappeared after depleting the intestinal flora.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatoprotective roles of probiotics and their protective mechanism against APAP hepatotoxicity have been revealed in different preclinical studies [ 78 , 79 , 80 , 81 ]. In these reports, different probiotic strains exhibited different mechanisms of hepatoprotection against APAP hepatotoxicity.…”
Section: Protective Roles Of Probiotic Strains Against Apap Hepatotox...mentioning
confidence: 99%
“…In addition to their inherent mechanisms, such as reconditioning gut microbiota, maintaining a healthy gut barrier, improving ATP production, and preventing negative metabolic effects, probiotics also ensured antioxidant, immunomodulatory, and anti-inflammatory mechanisms to counteract APAP hepatotoxicity. Moreover, probiotics have been shown to regulate various signaling events against APAP hepatotoxicity [ 73 , 81 ]. A few reports showed that a few probiotic strains can interfere with the pharmacokinetics of APAP [ 75 ].…”
Section: Protective Roles Of Probiotic Strains Against Apap Hepatotox...mentioning
confidence: 99%
See 1 more Smart Citation